Kajian Pola Pengelolaan Keuangan Badan Layanan Umum Daerah Puskesmas Pekalongan dengan Sistem Holding - Erny Riana Wafumilena; Minnalia Soakakone; S.A. Nugraheni Nugraheni (Center for Health Policy and Management, 2019)
Background: Management of Puskesmas needs a attention, especially with regard to the quality of health services. One form of management of public services that is appropriately applied to Puskesmas is the Regional Public Service Agency. An analysis of the current conditions and the continuity of the Regional agency of public service in Puskesmas requires further study to formulate the identification of problems and root causes in the management of Pekalongan City PPK-BLUD Holding and then look for solutions. Objective: Analyze and review the management of BLUD in the Pekalongan City Health Center. Method: This study uses a qualitative design through in-depth interviews and observations. Approach to the time of data collection and retrieval of data on the main informant and triangulation is not time-limited according to the adequacy of the data needed. The time of the study began in January 2019 with the subjects selected by purposive sampling, the subjects of the study were the Head of the Office, the Head of the Puskesmas, staffing staff, the Director of the BLUD, the BLUD secretary. Research for data management and analysis by means of data collection, data reduction, data presentation, drawing conclusions. Results: The Puskesmas in Pekalongan City with the status of BLUD began in 2014. The Pekalongan City Health Center with a holding system of 14 Puskesmas. The legal basis used is the Minister of Home Affairs Regulation No. 61 of 2007 concerning the Technical Guidelines for Financial Management of Regional Public Service Agencies which subsequently become the basis of Regulation No. 3 of 2015 concerning Governance in Pekalongan City Health Centers. The principle of mutual cooperation, cross-subsidies based on priority as a large family is a consideration for the implementation of Pekalongan City Health Center holding system. Another matter that was taken into consideration was the incorporation of BLUD governance with the establishment of 2 new Puskesmas in Pekalongan city that did not yet have membership in the National Health Insurance members so that the Puskesmas could not operate optimally related to income. Conclusion: Permendagri Number 79 Year 2018 becomes the basis for reviewing the pattern of financial management of the BLUD holding system in Pekalongan city in a flexible manner with the aim of providing more effective, efficient, economical, transparent and accountable public services.